IMPROVING THE METHODOLOGY FOR AUDITING ASSET IMPAIRMENT - Sayfullayev Mekhroj Sayfullayevich (Scholar Express Journals, 2025)
This article provides suggestions and recommendations for improving the methodology for auditing asset impairment in our country's accounting and auditing system, based on international practice.
Keywords: control test question; audit evidence; value in use